A Comprehensive Review of Thermosensitive Hydrogels: Mechanism, Optimization Strategies, and Applications - Tianyang Lv; Yuzhu Chen; Ning Li; Xiaoyu Liao; Yumin Heng; Yayuan Guo; Kaijin Hu (Gels, 2025)
Thermosensitive hydrogels undergo reversible sol-gel phase transitions in response to changes in temperature. Owing to their excellent biocompatibility, mild reaction conditions, and controllable gelation properties, these hydrogels represent a promising class of biomaterials suitable for minimally invasive treatment systems in diverse biomedical applications. This review systematically summarizes the gelation mechanisms of thermosensitive hydrogels and optimization strategies to enhance their performance for broader application requirements. In particular, we highlight recent advances in injectable thermosensitive hydrogels as a carrier within stem cells, bioactive substances, and drug delivery for treating various tissue defects and diseases involving bone, cartilage, and other tissues. Furthermore, we propose challenges and directions for the future development of thermosensitive hydrogels. These insights provide new ideas for researchers to explore novel thermosensitive hydrogels for tissue repair and disease treatment.